Bachok-Hasham polynomials for solving a special class of singular integral equations - Eshkuvatov Z.; Alhawamda H.; Ibrahim R.I.; Bachok M. Taib (American Institute of Physics Inc., 2024)
In this note, we propose a new class of orthogonal polynomials (named Bachok-Hasham polynomials of the first and second kind for order k, denote it as Z(i,n)k(x), i={ 1,2 }, which is extension of the Chebyshev polynomials of the first and second kind respectively. It is found that Bachok - Hasham polynomials of first and second kind Z(i,n)k(x) are orthogonal with respect to weights w(1,k)(x)=xk-11-x2k, w(2,k)(x)=xk-11-x2k on the interval [-1,1], where k is positive odd integers. Spectral properties Bachok - Hasham polynomials of the first and second kind Z(i,n)k(x),i={ 1,2 } are proved. These properties are used to solve a special class of singular integral equations. Finally, numerical examples and comparison results with other methods are provided to illustrate the effectiveness and accuracy of the proposed method. 2018 Author(s).